2020
DOI: 10.3906/sag-1912-242
|View full text |Cite
|
Sign up to set email alerts
|

Mean platelet volume and response to the first line therapy in newly diagnosed adult immune thrombocytopenia patients: a retrospective study

Abstract: Background/aim: Immune thrombocytopenia (ITP) is treated by corticosteroids and/or intravenous immune globulin as the first line treatment when necessary. Mean platelet volume (MPV) is a marker of platelet production and function. In this study, we aimed to search the relationship between the MPV and the treatment response in ITP patients and it was hypothesized that MPV can be used as a predictor of the response. Materials and methods:The 70 newly diagnosed adult primary ITP patients and 70 of healthy people … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…A high MPV indicates high platelet production, and a low MPV indicates low platelet production [23,24]. A previous study revealed that newly diagnosed adult patients with primary ITP with high baseline MPV were more likely to respond to firstline treatment [12]. However, our results revealed that patients with a lower baseline MPV were more responsive to rhTPO treatment, inconsistent with the results of a previous study.…”
Section: Table 4 Outcomes In Rhtpo Groupcontrasting
confidence: 99%
See 1 more Smart Citation
“…A high MPV indicates high platelet production, and a low MPV indicates low platelet production [23,24]. A previous study revealed that newly diagnosed adult patients with primary ITP with high baseline MPV were more likely to respond to firstline treatment [12]. However, our results revealed that patients with a lower baseline MPV were more responsive to rhTPO treatment, inconsistent with the results of a previous study.…”
Section: Table 4 Outcomes In Rhtpo Groupcontrasting
confidence: 99%
“…Moreover, the clinical predictors associated with the therapeutic effects of rhTPO remain unclear. Studies have demonstrated a correlation of mean platelet volume (MPV) [12,13] and platelet-to-lymphocyte ratio (PLR) [14,15] with the efficacy of treatment in ITP patients. However, to our knowledge, no studies have investigated the relationship between these predictors and the therapeutic efficacy of rhTPO in pregnant patients with ITP.…”
Section: Introductionmentioning
confidence: 99%
“…Another literature study 18 showed that impaired megakaryopoiesis in aplastic anemia (AA) and acute leukemia (AL) with thrombocytopenia had no change in MPV levels and that MPV was higher in ITP patients than in AA and AL patients. The results of Akkuş et al 19 pointed out that MPV can be used as a predictor of early response to first-line treatment in newly diagnosed adult ITP patients. The above analysis shows that MPV and P-LCR% can be used as clinically valuable biological parameters for the diagnosis, differential diagnosis, and efficacy evaluation of ITP.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 171 patients with thrombocytopenia, 4 out of 37 patients with ITP, the MPV was not elevated, though the highest values were found in ITP with a P value of less than 0.0001 [12]. The MPV in patients with ITP and healthy population was not very different ( P value 0.76) but high MPV had better outcome in patients with ITP [14]. The MPV cannot be measured accurately with very low platelet count as the analyzer may be unable to derive the MPV because of the platelet histogram distribution.…”
Section: Resultsmentioning
confidence: 92%